Hemopexin therapy reverts heme-induced proinflammatory phenotypic switching of macrophages in a mouse model of sickle cell disease - Vinchi, Francesca; Costa da Silva, Milene; Ingoglia, Giada; Petrillo, Sara; Brinkman, Nathan; Zuercher, Adrian; Cerwenka, Adelheid; Tolosano, Emanuela; Muckenthaler, Martina (Blood, 2016)
Key Points. Heme and iron induce macrophage phenotypic switching toward an M1 proinflammatory phenotype.By scavenging free heme, hemopexin reverts heme-induced
Gesehen am 04.06.2020